2018
DOI: 10.1186/s12862-018-1309-8
|View full text |Cite|
|
Sign up to set email alerts
|

Classification, substrate specificity and structural features of D-2-hydroxyacid dehydrogenases: 2HADH knowledgebase

Abstract: BackgroundThe family of D-isomer specific 2-hydroxyacid dehydrogenases (2HADHs) contains a wide range of oxidoreductases with various metabolic roles as well as biotechnological applications. Despite a vast amount of biochemical and structural data for various representatives of the family, the long and complex evolution and broad sequence diversity hinder functional annotations for uncharacterized members.ResultsWe report an in-depth phylogenetic analysis, followed by mapping of available biochemical and stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 113 publications
(240 reference statements)
1
24
1
Order By: Relevance
“…Our phylogenetic analysis (Fig. S4 ) indicates that the enzyme is a bona fide NAD + -dependent Fdh within the superfamily of D-2-hydroxyacid dehydrogenases [ 76 ]. This indicates the capacity to use formate for supplementing CO 2 needs while concomitantly supplying reducing equivalents (as in methylotrophs [ 77 , 78 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Our phylogenetic analysis (Fig. S4 ) indicates that the enzyme is a bona fide NAD + -dependent Fdh within the superfamily of D-2-hydroxyacid dehydrogenases [ 76 ]. This indicates the capacity to use formate for supplementing CO 2 needs while concomitantly supplying reducing equivalents (as in methylotrophs [ 77 , 78 ]).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, these five residues are also structurally conserved and fully buried in the interface among the SerA subfamily via structure-based sequence alignment with known PGDH structures (PDB codes: 2G76 , 4NJO , 1YBA , 1YGY , 3K5P , 1WWK , and 2EKL ) ( Fig. S2 ) ( 20 , 23 , 39 , 40 ). Protein–protein interaction studies have suggested that hot spots are likely to be structurally conserved residues and are organized in high packing density regions.…”
Section: Resultsmentioning
confidence: 99%
“…PHGDH belongs to the SerA subset of D-isomer-specific 2-hydroxyacid-dehydrogenase (2HADH) family that catalyzes the stereospecific reductions of 2-keto acids to corresponding 2-hydroxy acids ( 20 ). D-3-phosphoglycerate dehydrogenases (PGDHs) expressed in various organisms are grouped into three types based on their domain arrangement.…”
mentioning
confidence: 99%
“…The ribose of the adenosine moiety is bound by two hydrogen bonds with the conserved, negatively charged side chain of D45, suggesting the enzyme has a strong preference for NAD + . Binding of the 2′‐phosphate of NADP + is likely prevented due to the steric interference and the negative charge of D45, as is observed in many TyrA proteins and other NAD + /NADP + ‐dependent dehydrogenases . Altogether, the overall fold of BaPDH's catalytic core is highly similar to other bacterial PDHs as represented by AaPDH (Fig.…”
Section: Resultsmentioning
confidence: 79%